Effect of accelerating the nickel ore export ban on the sustainability of international business transactions for Indonesia - Julastrid Jelita Katili (The International Journal of Politics and Sociology Research, 2023)
The continuous export of nickel ore has resulted in its own impact on Indonesia, such as the depletion of nickel ore contained in it, thus the Government of Indonesia began to take steps to downstream and industrialize the raw materials of natural resources owned by Indonesia and stop sending nickel ore materials abroad. The government through the Ministry of Energy and Mineral Resources issued Minister of Energy and Mineral Resources Regulation 11/2019, which decided to accelerate the ban on nickel ore exports. The legal issue is whether the nickel ore export ban by the Indonesian government is in accordance with the Constitution? How is the impact of the Nickel Ore Export Ban policy based on Minister of Energy and Mineral Resources Regulation No. 11 of 2019 on international trade? The writing of this article uses normative juridical research. The results of the study The government as a representation of the state has an obligation to protect and maintain the resources within the country. Indonesia's involvement in the International Trade Organization is a form of Indonesia's openness in international trade activities and encourages economic growth. The ban on nickel ore exports issued by the Government of Indonesia which was then tried in the WTO panel which emphasized in its decision that the policy was contrary to the rules of the GATT, Indonesia in this case continued to take the appeal route.